Zinc alloys as prospective materials for biodegradable medical devices - Kubasek, Jiri; Dvorsky, Drahomir; Capek, Jaroslav; Marketa, Strakova; Klara, Hosova; Vojtech, Dalibor (Manufacturing Technology Journal, 2020)
Zinc-based materials are considered as promising materials for an application like biodegradable medical devices (bone fixations, stents). Such materials have to be characterized by an excellent combination of me-chanical, corrosion and biological properties. Presented paper is focused on the characterization of micro-structure and closely related mechanical properties for 3 zinc materials, namely pure Zn, Zn-0.8Mg and Zn-0.8Mg-0.2Sr. Studied alloys were prepared by gravity casting, homogenization treatment at 350 °C and extru-sion at 200 °C and extrusion ratio 11. Alloying by Mg caused the refinement of microstructure, formation of Mg2Zn11 phase and related improvement of mechanical properties like TYS and UTS for an extruded alloy. An additional encore of Sr causes a systematical improvement of TYS and UTS values, although the elonga-tion vas slightly decreased due to the presence of brittle SrZn13 phase.
Keywords: Zinc; magnesium; biodegradable materials; mechanical properties